Administrasi Islam di Indonesia - Wisber Wiryanto (Restorica: Jurnal Ilmiah Ilmu Administrasi Negara dan Ilmu Komunikasi, 2020)
Deliar Noer in the book Administration of Islam in Indonesia published in the 1980s early, discussed the problems of the ministry of religion, Islamic education, Islamic law and religious court, Hajj pilgrimage as well as Indonesian Ulema Councils. Furthermore, it is necessary to review the problem in the present. With problem formulation, how do the development administration of Islam in Indonesia current? The aims of this research to identify the development administration of Islam in Indonesia current. The research was conducted using an explanative-descriptive method with the object of Islamic administration; while the subject/ source of data is references related to administration of Islam in Indonesia. The results showed the problems of the ministry of religion, Islamic education, Islamic law and religious court, hajj pilgrimage as well as Indonesian ulema councils. A solution is needed to address the cause of problem by reform the administration of Islam in Indonesia.